2004
DOI: 10.2298/jsc0411955i
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and pharmacological evaluation of (±)-2, 3- seco-fentanyl analogues

Abstract: An efficient, five-step synthetic approach to various acyclic 1,3-diamines has been developed and applied to the preparation of a novel class of open-chained fentanyl analogues. The acyclic derivatives 5.1?5.5 (all new compounds) were synthesized with the aim of estimating the significance of the piperidine ring for the opioid analgesic activity of anilido-piperidines. The starting ?-keto-amide 1.1, prepared by the aminolysis of methyl acetoacetate with methylphenethylamine, (93 % yield), was successively reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, the synthesis of F02 was reported before [ 41 ], however no data as to its analgesic activity or opioid receptor affinity were disclosed. The here presented binding data are in line with pharmacological characteristics of another acyclic derivative 2,3-seco-fentanyl for which it was found that it is about 40 times weaker an analgesic than fentanyl [ 42 ].…”
Section: Resultssupporting
confidence: 82%
“…To the best of our knowledge, the synthesis of F02 was reported before [ 41 ], however no data as to its analgesic activity or opioid receptor affinity were disclosed. The here presented binding data are in line with pharmacological characteristics of another acyclic derivative 2,3-seco-fentanyl for which it was found that it is about 40 times weaker an analgesic than fentanyl [ 42 ].…”
Section: Resultssupporting
confidence: 82%
“…One of them, diampromide ( 1S ) which produces effects similar to other opioid analgesics, and is around the same potency as morphine with an ED 50 of 4 mg/kg [71,72], another is 2,3-seco-fentanyl ( 2S ) whose central-analgesic activity was found to be 40-times lower than fentanyl, but still 5–6-times higher than that of morphine (Supplementary Information 2)[73]. …”
Section: Synthesis and Biological Activity Of Compounds In The Fentanylmentioning
confidence: 99%
“…120 times more potent than the (-)-enantiomer and 16-19 times more potent than both the (±)-trans-diastereomer and fentanyl. 7 Voluminous 3-alkyl groups reduce the activity, 5,8 and a 3-carbomethoxy function confers potency similar to that of fentanyl 9a,10 while 3-hydroxy, 11,12 3-methoxy, 13 and 3-fluorine 14 substituents were not evaluated pharmacologically.…”
mentioning
confidence: 99%